Determination of the role of synechococcus rubisco residue val-425 in chimeras - Wong, Clara Chia Ci (2023)
Ribulose-1,5-bisphosphate carboxylase/oxygenase (EC 4.1.1.39), Rubisco is one of the most extensively studied enzymes due to its abundance on Earth and its significance in the food supply chain. As the rate-limiting enzyme in the Calvin cycle, the catalytic inefficiency of Rubisco has led to an undesirable side reaction known as photorespiration that compromises the carboxylase activity of CO2 fixation, thus, making it the primary target for bioengineering to improve its catalytic efficiency. Innovative approaches were made by researchers to improve the carboxylation capacity of Rubisco which nonetheless was hampered by the unsuccessful heterologous formation of functional Rubisco enzyme, plausibly due to incompatible assembly pathways. Previous findings by Koay, Wong and Lim (2016) were extended in this study whereby the chimeric mutant bearing mutated residue 425 (Thr-425) is used as the target for site-directed mutagenesis (SDM) that reverts the Thr mutation to Val residue. The current study explores the potential role of Val-425 in the large subunit (RbcL) of Synechococcus Rubisco that is previously hypothesized to be critical for the chaperone-mediated assembly of the holoenzyme. SDM had successfully restored Val residue at position 425 of RbcL which was validated by restriction iii digestion of PstI enzyme. Expression for both Rubisco subunits (RbcL and RbcS) upon SDM was detected on SDS-PAGE at 55 kDa and below 15 kDa, respectively. Furthermore, Val-425 is also found to be important in conferring stability in the native conformation of Synechococcus RbcL and its contribution to greater hydrophobicity suggests its associated role in chaperonin-binding.